Time Preference and Natural Resource Use by Local Communities: The Case of Sinharaja Forest in Sri Lanka - H. M. Gunatilake; W. A. R. Wickramasinghe; P. Abeygunawardena (Asian Development Bank (ADB), 2007)
Empirical studies on the impact of the individual rate of time preference (IRTP) on natural resource use are scarce. This paper investigates the impact of IRTP on forest resources harvesting from the Sinharaja Man and Biosphere Reserve in Sri Lanka. The impact of IRTP on the harvest rate of forest resources was tested using a simultaneous equation model. Analysis of the determinants of IRTP shows that the base value and age of the respondents negatively influence the IRTP while risk perception positively influences the IRTP. More importantly, low income induces a higher IRTP, indicating that poverty is an important determinant of the IRTP. Further, the results show that individuals with a higher rate of time preference harvest more forest resources. Overall, the results suggest that long-term strategies for management of nature reserves would require poverty alleviation in the peripheral communities, among other measures.
hdl:11540/1860
Keywords: 330; Intertemporale Entscheidung; Wald; Schätzung; Sri Lanka